Military Hospital of San Miguel (1838-1839) - Esperanza Santano Mogena; Sergio Rico Martín; María Luz Sánchez Calvarro; Julián Fernando Calderón García (Universidad de Alicante, 2015)
The settlement of several infantry and cavalry regiments in the area of Trujillo led the general captain to install a Hospital in the town. Such hospital was placed in San Miguel's convent, since it was unoccupied. The three physicians, a pharmacist and the nursery assistant of Trujillo rendered service at the hospital, together three nurses hired to attend military patients. The Province Council of Caceres was encharged of supply the hospital material necessities, and the City Council beared the cost of expenses and staff salary. As the recordings shown, 93 military patients and one prisioner were attended at the hospital in a three-months period, rendering 1714 days of internment. San Miguel Hospital was operative for two years, being closed at the end October 1839. Objectives: to determine the staffing of the institution, focusing on the figure of the nursing staff; exposing the materials that had the care team to give such care and attention given to describe the military patients who were admitted to the hospital resources. It has made a historical documentary study for the years 2013-2014, of the files that are deposited in the Municipal Archives of Trujillo. Following this research we can conclude that the figure of the nurses was crucial in the functioning of the Military Hospital of San Miguel, because this group is responsible for providing the necessary care for military patients towards recovery. Were entities like the County and the City of the city which covered the cost that it originated.